Respons Audiens terhadap Jenis Alih Kode dalam Video Pembelajaran Bahasa Arab di Kanal YouTube Arab Podcasts - Abqari, Rafid Gastiadirrijal Muhammad; Supriadi, Rinaldi; Khalid, Shofa Musthofa (Study Program of Arabic Language Teaching, 2026)
This study aims to analyze the cognitive responses and processing fluency of audiences toward intra-sentential, inter-sentential, and tag-switching code-switching on the YouTube channel